The role of segregation in the polarized emission from polyfluorene embedded in a liquid crystal. Issue 16 (18th April 2016) - Ghirardini, Lavinia; Virgili, Tersilla; Bolis, Serena; Beeckman, Jeroen; Kockaert, Pascal; Finazzi, Marco; Celebrano, Michele
ABSTRACT: Polyfluorene (PFO) embedded in a nematic liquid crystal (LC) matrix is investigated. For low PFO weight contents, a homogeneous dispersion is obtained which displays a strong fluorescence anisotropy along the LC director, indicating a significant alignment of the polymeric chains along this direction. Besides, for relatively high PFO weight contents, phase separation takes place. Under these conditions, the sample is composed of micrometer‐sized domains, where the two species are in solution, enclosed by segregated polymeric boundaries. By polarized‐photoluminescence imaging and spectroscopy, it is found that most of the light emission originates from these boundaries and gets strongly pinned along their orientation. Since boundaries are mainly oriented orthogonal to the LC chains, this morphological alignment results in a system in which the orientation of the polarization emission can be predicted and possibly controlled. Conversely, in the homogeneous sample one can obtain a homogeneous emission polarization by controlling the alignment of the LC. These features are potentially relevant for the development of flexible polarization‐sensitive optoelectronic devices. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 1558–1563 Abstract : In the investigation of polyfluorene embedded in a nematic liquid crystal matrix at different weight contents, different morphologies are observed: a homogeneous one and an inhomogeneous one. By correlating the sample structure with polarized‐photoluminescence imaging and spectroscopy, it is discovered that each different morphological alignment results in a system in which it is possible to predict and eventually control the orientation of the polarization emission. These features are potentially relevant for the development of flexible polarization‐sensitive optoelectronic devices.